Gambaran Umum, Prevalensi, dan Pencegahan Antraks pada Manusia di Indonesia - Ihda Zuyina Ratna Sari; Silvia Apriliana (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2020)
Anthrax is a neglected zoonotic disease that remains a global issue because it can cause regular epidemics. Anthrax affects not only health systems but also social-economic conditions, safety, and welfare of the people. This paper aimed to give an overview of human anthrax, prevalence, and prevention in Indonesia. A literature search was performed using search engines such as Google Scholar, Crossref, Mendeley, PLoS One, Elsevier, dan the Ministry of Health official website. The literature used were published between 2015-2020. Anthrax is caused by Bacillus anthracis that affects animals and humans. The virulence factors of these bacteria are determined by the tripartite toxin complex and poly-γ-D-glutamic acid capsule. Anthrax in humans can be found in four forms, namely cutaneous, gastrointestinal, inhalational, and injection anthrax. Each form of anthrax can develop into meningitis and sepsis. Anthrax treatment is commonly done by administering antibiotics. In Indonesia, 14 provinces have been declared anthrax endemic areas. The prevalence of human anthrax in Indonesia is fluctuating and most of it is cutaneous anthrax. Prevention and control of anthrax can be done mainly by vaccination, obeying the rules or standard operating procedures of the authorities, multisectoral cooperation, strengthening anthrax surveillance, increasing resources for diagnosis, increasing public knowledge, and awareness.